2009
DOI: 10.1111/j.1365-2214.2009.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the medically unexplained: emotional and familial influences on children's somatic functioning

Abstract: These results suggest that models of child somatization should consider both family - (e.g. parent somatization) and child-level (e.g. emotional functioning) variables. The discrepancies between parent and child report of youth somatic symptoms underscore the importance of including multiple reporters on symptomatology in research and clinical settings. Suggestions for future research are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
5
24
0
7
Order By: Relevance
“…Similarly, mothers may report more child somatic symptoms than fathers [36], and parental somatization can lead to the development of somatization in children [37]. The PHQ-15 potentially provides a useful measure of somatic symptoms in perinatal samples based on the current findings with postpartum women.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, mothers may report more child somatic symptoms than fathers [36], and parental somatization can lead to the development of somatization in children [37]. The PHQ-15 potentially provides a useful measure of somatic symptoms in perinatal samples based on the current findings with postpartum women.…”
Section: Discussionmentioning
confidence: 86%
“…Because somatic problems in early childhood have been found to persist into middle childhood and adulthood (Pihlakoski et al, 2006), and also predict externalizing and internalizing disorders, providing preschool children with interventions to reduce somatic symptoms is encouraged (Gilleland et al, 2009). In addition, this study confirms results of previous research that indicate CCPT is effective in reducing problematic classroom behaviors of preschool and elementary students (Bratton et al, 2013;Fall et al, 2002;Garza & Bratton, 2005;Schottelkorb & Ray, 2009;Schumann, 2010;Swan & Ray, 2014).…”
Section: Implications For Counselorsmentioning
confidence: 99%
“…Gilleland, Suveg, Jacob, and Thomasson (2009) speculated that an overall lack of awareness of emotions could be related to somatic symptomology. In their investigation of 42 children, ages 7 to 12, Gilleland and colleagues (2009) found that faulty selfawareness and heightened negative affect predicted children's reporting of somatization symptoms.…”
mentioning
confidence: 99%
“…Child characteristics, including poor emotional awareness and frequent negative affect, correlate with child-reported somatic symptoms. 4 Pediatric patients may lack awareness of emotions; instead of perceiving that they are anxious, they perceive that their stomach hurts. This is most notable in patients with recurrent abdominal pain, whereas patients with other somatic complaints, such as fatigue, musculoskeletal pain, or headache, are more emotionally aware and report symptoms associated with depression and anxiety.…”
Section: Case 1: Child Focusedmentioning
confidence: 99%